Advanced nanoelectronics - Bin Ismail, Razali; Ahmadi, Mohammad Taghi; Anwar, Sohail (Boca Raton, FL : Taylor & Francis, 2013)
'With a focus on current research, this book covers nanodevice characteristics, state-of-the-art techniques used for nanodevice modeling, and applications of these models in diverse disciplines of science and engineering. The text first offers an introduction to the basic concepts of nanoelectronics, nanoscale device modeling, and nanoquantum fundamentals. Then, it discusses in detail nanodevice characteristics and nanoscale device models. It also presents an extensive discussion of graphene nanoribbon technology as well as graphene nanoribbon based models. In addition, the authors describe key concepts of quantum computing and quantum nanodots'--
Includes bibliographical references and index.
Keywords: Nanoelectronics